The Protection Of Customary Law Communities At The National And International Level (Post The Issue Of Law No: 1 Of 2023 Concerning The Criminal Law Book) - Setiawati, Agnes; Firmanto, Aditia Arief; Rahmad, Dewi Muslimah; Sundari, Esti (Universitas Malayati, 2024)
The 2023 reform of Indonesia's Criminal Code aims to improve the protection of society from crime, including immoral acts and modern crimes. A number of new articles, including those governing adultery and LGBT, are expected to provide substantial justice and adapt the law to the dynamics of society. The research method used is qualitative with a literature study. Although the new Criminal Code recognizes the rights of indigenous peoples, challenges in implementation still exist. Unequal access to justice, financial constraints, and inadequate legal representation are some of the obstacles that need to be overcome. It is important to ensure the Criminal Code's compatibility with existing international legal instruments related to community rights, such as the UN Declaration on the Rights of Indigenous Peoples (UNDRIP) and ILO Convention No. 169. Robust reporting and monitoring mechanisms are needed to ensure the sustainability of the implementation of the Penal Code and involve the active participation of indigenous peoples. Potential international litigation Indonesia must ensure the protection of customary law in the Criminal Code does not violate international standards. The successful implementation of the Criminal Code depends on cooperation between the government, indigenous peoples, and law enforcement agencies.Keywords: Justice, Criminal Code, UNDRIP